Differential Cannabinoid Receptor Expression during Reactive Gliosis: a Possible Implication for a Nonpsychotropic Neuroprotection - Daniele De Filippis; Antonio Steardo; Alessandra D'Amico; Caterina Scuderi; Mariateresa Cipriano; Giuseppe Esposito; Teresa Iuvone (The Scientific World Journal)
Activated microglia and astrocytes produce a large number of inflammatory and neurotoxic substances in various brain pathologies, above all during neurodegenerative disorders. In the search for new neuroprotective compounds, interest has turned to marijuana derivatives, since in several in vitro, in vivo, and clinical studies, they have shown a great ability to control neuroinflammation.